2018
DOI: 10.1371/journal.pone.0206004
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of pharmaceuticals and other micropollutants in groundwater downgradient from large on-site wastewater discharges

Abstract: Large subsurface treatment systems (LSTS) and rapid infiltration basins (RIB) are preferred onsite wastewater treatments compared to direct discharge of treated wastewater to streams and adjacent facilities. Discharge of these wastewater treatments may result in contaminant loading to aquifers that also serve as drinking water sources downgradient from the discharge site. Until recently, few studies have characterized the contribution of micropollutants (e.g. pharmaceuticals, fragrances, flame retardants, etc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…[1][2][3] Therefore, hyphil-TrOCs are ubiquitous in surface waters and groundwater and have been also detected in finished drinking water. 1,[3][4][5][6][7][8] Numerous hyphil-TrOCs cause biological effects such as endocrine disruption at trace concentrations, which pose risks to ecosystem and human health. 9,10 One major point source of hyphil-TrOCs are effluents from conventional wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Therefore, hyphil-TrOCs are ubiquitous in surface waters and groundwater and have been also detected in finished drinking water. 1,[3][4][5][6][7][8] Numerous hyphil-TrOCs cause biological effects such as endocrine disruption at trace concentrations, which pose risks to ecosystem and human health. 9,10 One major point source of hyphil-TrOCs are effluents from conventional wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, diversos trabalhos recentes têm demonstrado a aplicabilidade de traçadores para diagnosticar inequivocamente a contaminação por fossas sépticas. Destacandose adoçantes como (van STEMPVOORT et al 2011;KHAZAEI e MILNE-HOME, 2017;SPOELSTRA et al 2017) ou fármacos diversos (SCHAIDER et al 2016;ELLIOTT et al 2018, DODGEN et al 2017LEE et al 2019). Por esta razão, o emprego destes traçadores pode representar uma importante alternativa para avaliar as transformações hidroquímicas que podem ser associadas à contaminação por fossas sépticas em áreas carentes de saneamento básico.…”
Section: Discussionunclassified
“…Many researchers investigated the source of the PPCPs, and it is shown that the discharge from wastewater treatment facilities and septic systems contribute as the major portion of these contaminations. In a study conducted by Elliott, Erickson, Krall, and Adams (2018) on water quality of downgradient wells from five large subsurface treatment systems (LSTS) and two rapid infiltration basins (RIB), a total of 18 pharmaceuticals out of 223 micropollutants were detected with concentrations ranging between 90 and 4,039 ng/L. Three primary pharmaceuticals, including fluconazole as antifungal, carbamazepine as anticonvulsant, and sulfamethoxazole as antibiotics, were the most detected constituents in the groundwater samples.…”
Section: Groundwater Pollutionmentioning
confidence: 99%